Women’s Motivation for Joining the Maoist Movement in Nepal: A Study of Ex-PLA Participants in Janaki Rural Municipality, Kailali - Adhikari, Kanshi Prasad (Academia Research Journal, 2023)
This research aims to investigate the motivations of women for joining the Maoist movement and strives to challenge outdated beliefs about women’s issues. It delves into their socio-cultural, economic, and educational backgrounds, as well as their pursuit of gender equality, leadership, and self-worth while working alongside men on equal terms. The study focuses on 15 Ex-PLA women in Janaki Rural Municipality, employing a purposive sampling method and an anthropological approach involving interviews and observations. The research unravels the challenges in analyzing female participants’ experiences and opinions, considering the sensitivity and confidentiality of the subject matter and the cautious approach to human rights and privacy. The discussion reveals the deeply entrenched patriarchal system in Nepal, which has historically relegated women to a subordinate position and deprived them of power and knowledge creation. Despite legislative measures granting women citizenship and some representation, informal barriers and societal attitudes continue to impede their progress. The study highlights various factors motivating women to join the Maoist movement in Janaki Rural Municipality, including the historical patriarchal nature of Nepal, limited property rights for women, extended male absences, the dual burden of coordinating with both Maoist and security forces, and the impact of the Kilosera-2 operation’s brutality and upheaval. Ultimately, this research sheds light on the transformative potential of women when given opportunities and challenges the prevailing societal norms, offering insights into the factors driving their participation in the Maoist movement and advocating for their rights and recognition on equal footing with men.